Penta-deuterium-labeled 4E, 8Z-sphingadienine for rapid analysis in sphingolipidomics study. (July 2022) - Murai, Yuta; Yuyama, Kohei; Mikami, Daisuke; Igarashi, Yasuyuki; Monde, Kenji
Abstract: The use of deuterium-incorporated bioactive compounds is an efficient method for tracing their metabolic fate and for quantitative analysis by mass spectrometry without complicated HPLC separation even if their amounts are extremely small. Plant sphingolipids and their metabolites, which have C4, 8-olefins on a common backbone as a sphingoid base, show unique and fascinating bioactivities compared to those of sphingolipids in mammals. However, the functional and metabolic mechanisms of exogenous plant sphingolipids have not been elucidated due to the difficulty in distinguishing exogenous sphingolipids from endogenous sphingolipids having the same polarity and same molecular weight by mass spectrometric analysis. Their roles might be elucidated by the use of deuterated probes with original biological and physicochemical properties. In this study, we designed (2 S, 3 R, 4 E, 8 Z )-2-aminooctadeca-4, 8-diene-17, 17, 18, 18, 18- d 5 -1, 3-diol (penta-deuterium-labeled 4 E, 8 Z -sphingadienine) as a tracer for exogenous metabolic studies. In addition, the sphingadienine was confirmed to be metabolized in HEK293 cells and showed distinct peaks in mass spectrometric analysis. Graphical Abstract: ga1 Highlights: This is the first report for preparing (2S, 3R, 4E, 8Z)-2-aminooctadeca-4, 8-diene-17, 17, 18, 18, 18- d 5 -1, 3-diol (penta-deuterium-labeled 4 E, 8 Z -sphingadienine). Penta-deuterium-labeled 4 E, 8 Z -sphingadienine is useful for understanding its metabolic fates by sphingolipidomics. Quantitative analysis for various Cer, HexCer, and SM classes derived from penta-deuterium-labeled 4 E, 8 Z -sphingadienine is also conducted without a complicated HPLC technique.